An ultrafast spectroscopic and quantum mechanical investigation of multiple emissions in push–pull pyridinium derivatives bearing different electron donors. Issue 32 (28th August 2015) - Carlotti, B.; Benassi, E.; Cesaretti, A.; Fortuna, C. G.; Spalletti, A.; Barone, V.; Elisei, F.
<x xml:space="preserve">Abstract</x> An interconversion between rotamers in S1 was evidenced for a cationic push–pull pyrenyl derivative through a joint femtosecond fluorescence up-conversion and density functional theoretical study.